The tensions of innovation: experiences of teachers during a whole school pedagogical shift. Issue 2 (3rd March 2020) - Knight, Rupert
ABSTRACT: Education in many countries is heavily influenced by what has been termed a Global Education Reform Movement, based on competition, measurement and comparison. As well as emphasising external accountability, this landscape offers schools, in theory, a degree of autonomy. School-level innovation, however, may involve a degree of courage on the part of teachers if this involves stepping away from the safety of an agenda based on externally measured standards. By documenting the voices of teachers throughout a year of pedagogical innovation in one school in England, this study aims to reveal what it is like to be a teacher experiencing an inspiring but challenging form of school-level change. The multi-faceted experiences of the teachers are characterised as three tensions centred on autonomy, innovation and collaboration. The study suggests that the innovation in question did result in a feeling of transformation in a variety of forms. However, this transformation was limited by various factors, such as the need for a stronger collaborative response to challenges of 'unlearning' deeply ingrained practices and, above all, the enduring spectre of external scrutiny. The authentic voices of these teachers provide an insight into the issues that schools must consider when exercising their autonomy and implementing 'brave' pedagogical innovations.